Second law of thermodynamics and urban green infrastructure - A knowledge synthesis to address spatial planning strategies - Pelorosso, Raffaele; Gobattoni, Federica; Ripa, Maria Nicolina; Leone, Antonio (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Planning of ecosystem services provided by the Urban Green Infrastructure (UGI) is a key issue for urban sustainability. Planning strategies driven by the second law of thermodynamics (SLT) are innovative approaches to sustainability but they are still in seminal phase. In this article, a coupled review of SLT within spatial planning is accomplished looking at the main applications in urban green infrastructure (UGI) planning. The work has supported the definition of a preliminary low-entropy UGI planning strategy (Pelorosso, Gobattoni, & Leone, 2017) but it also aims to contribute to the improvement and/or development of even more solid planning strategies based on SLT. In particular, a systemic review of UGI planning and thermodynamics has been carried out to identify all the occurrences to date in the scientific literature. Secondly, a scoping review of SLT-related concepts of exergy, entropy and urban metabolism is presented in order to investigate the main applications of, and gaps in, urban spatial planning. Results indicate that UGI and ecosystem service planning based on SLT is a relatively new field of research. Moreover, some general indications are derived for the development of spatial UGI planning strategies based on SLT.